Control of ionization processes in magnetron sputtering system by changing magnetic field configuration - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Makhlai, V.A. (Вопросы атомной науки и техники, 2021)
This work is devoted to measuring the function of the distribution of charged particles of gas-discharge plasma in a magnetron sputtering system under conditions of non-potential “earth”. Measurements are carried out with the help of a three-electrode probe, which is installed in the cathode sputtering zone, with unsafe electrodes and housing. The selection of the analyzed particles was carried out through a screen located under floating potential. Effect of additional magnetic insulation anode of MSS МАG-5 on ion and electron distribution functions was investigated.